2021
DOI: 10.1063/5.0042583
|View full text |Cite
|
Sign up to set email alerts
|

C-shaped chiral waveguide for spin-dependent unidirectional propagation

Abstract: Spin-dependent unidirectional propagation is one of the most intriguing features of the Quantum spin-Hall effect, which was studied intensively in electronic systems and led to the discovery of topological insulators. Recently, it was proven that evanescent waves intrinsically possess transverse spin that is dependent on the direction of propagation. This has enabled new applications in unidirectional waveguiding and integrated quantum optics. In this work, we study via numerical simulations a waveguide design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Despite electrons and photons being fundamentally different particles, they reveal similar spin-related properties, among which is the SHE. It was recently discovered that analogous to the SHE in electrons, surface waves (SWs) with evanescent tails obtain an in-plane transverse spin that is locked to the propagation direction. This is also known as spin-momentum locking, which is defined as the right-hand triplet formed from the decay constant, spin, and propagation constant. , During the past decade, several photonic platforms were shown to be able to control the propagation direction of surface waves through altering its transverse spin (T-spin). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite electrons and photons being fundamentally different particles, they reveal similar spin-related properties, among which is the SHE. It was recently discovered that analogous to the SHE in electrons, surface waves (SWs) with evanescent tails obtain an in-plane transverse spin that is locked to the propagation direction. This is also known as spin-momentum locking, which is defined as the right-hand triplet formed from the decay constant, spin, and propagation constant. , During the past decade, several photonic platforms were shown to be able to control the propagation direction of surface waves through altering its transverse spin (T-spin). …”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the fact that when the surface wave (which intrinsically has a transverse spin) interacts with a surface of a broken mirror inversion symmetry, it will result in spin-symmetry breaking where the left circularly polarized (LCP) field propagates in one direction and the right circularly polarized (RCP) field propagates in the opposite direction. This has been studied in the literature in various ways including designing metasurfaces or waveguides with engineered anisotropy, gradient metasurface designs, uniaxial hyperbolic metamaterials, and bandgap materials , or through inversion symmetry breaking by the near-field interference of a dipole source near the surface. , The ability to control the directionality and polarization of SWs by engineering the metasurface designs is pivotal for many applications in valleytronics and polarization-based optics such as beam splitting and spin-based waveguiding. , Many studies showed the significance of the shape symmetry in controlling the polarization of the reflected and transmitted waves through homogeneous and nonhomogeneous designs such as V-shaped, L-shaped, , and split ring resonator metasurfaces. , For the polarization control of surface waves, it was proven in ref that any SW obtains an in-plane T-spin. However, the out-of-plane T-spin does not naturally occur for SWs and needs to be extrinsically enforced by the design …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also known as spin-momentum locking which is defined as the right-hand triplet formed of the decay, spin and propagation constant [8,9]. During the past decade, several photonic platforms were shown to be able to control the propagation direction of light through altering its T-spin [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is believed to be very small and not easily observed unless enhanced by breaking the spatial inversion symmetry of the surface. This has been studied in the literature in various ways including designing metasurfaces or waveguides with engineered anisotropy [10][11][12][13][14], gradient metasurface designs [15] and bandgap materials [17,18] or through inversion symmetry breaking by the near-field interference of a dipole source near the surface [19,20]. The ability to control the directionality and polarization of SWs by engineering the metasurface designs is pivotal for many applications in valleytronics [21] and polarization-based optics such as beam splitting [22] and spin-based waveguiding [11,23].…”
Section: Introductionmentioning
confidence: 99%